2020
DOI: 10.2196/16254
|View full text |Cite
|
Sign up to set email alerts
|

Engaging African American Youth in the Development of a Serious Mobile Game for Sexual Health Education: Mixed Methods Study

Abstract: Background Although teen pregnancy rates decreased dramatically in the United States over the past decade, the rates of sexually transmitted infections (STIs) among adolescents and young adults increased. STI rates disproportionately affect African American youth and young adults. Innovative, accessible, and culturally relevant sexual health interventions are urgently needed. Objective This study aimed to identify the optimal modality for a game-based s… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
29
0
9

Year Published

2020
2020
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(40 citation statements)
references
References 13 publications
1
29
0
9
Order By: Relevance
“…This study found that gamified learning contents were experienced as “relevant.” For instance, the students realized that there was a common connection between what they were learning and real life. These results were consistent with an earlier study [ 19 ], which had indicated that gamifying sexual health learning approaches was promising for adolescents because the role plays and scenarios reflect the actual lifestyle of the current generation. The students felt confident while going through the self-regulated learning material provided through the gamified learning (which stimulated and sustained their learning).…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…This study found that gamified learning contents were experienced as “relevant.” For instance, the students realized that there was a common connection between what they were learning and real life. These results were consistent with an earlier study [ 19 ], which had indicated that gamifying sexual health learning approaches was promising for adolescents because the role plays and scenarios reflect the actual lifestyle of the current generation. The students felt confident while going through the self-regulated learning material provided through the gamified learning (which stimulated and sustained their learning).…”
Section: Discussionsupporting
confidence: 92%
“…SG and GM methods were found to be effective and efficient in increasing motivation, improving attitudes, increasing knowledge acquisition, and encouraging engagement in the learning process. Future empirical studies may verify the efficacy of the My Future Begins Today learning platforms in improving sexual health literacy acquisition in other countries, especially in SSA, where the TT method is widely practiced and tends to limit the learning with gamified digital technologies and process [ 19 , 25 ]. This paper also addresses more than ever the call from a previous study [ 25 ] to evaluate the effect of gamifying sexual health education when different key stakeholders are involved in the design process in low-tech settings.…”
Section: Discussionmentioning
confidence: 99%
“…In fact, there is an interplay between serious gamified elements, on the one hand and motivation and engagement, on the other hand, to make gamified learning effective (Buckley et al, 2018). According to Patchen et al (2020), if all aspects of serious gamified elements were embedded in the gamified system to enhance motivation and engagement, learning could then be improved and sync with 21st-century skills, such as collaboration, communication, problem-solving and critical and the ability for thinking strategically.…”
Section: Related Workmentioning
confidence: 99%
“…Engaging youths through PR can be successful for developing, implementing, and interpreting the results of research and can offer the potential to overcome the challenges of developing culturally and linguistically appropriate, community responsive interventions for underserved populations [ 41 ]. Moreover, as elucidated by Patchen et al [ 42 ], PR integrated with user-centered design methods offers practical, culturally relevant, and systematic guidance to develop appropriate interventions for underserved groups. Lastly, the use of abductive analysis provided a comprehensive method for developing graphic messages that were both empirically and theoretically grounded.…”
Section: Discussionmentioning
confidence: 99%